RANCANG BANGUN BANDPASS FILTER MIKROSTRIP MENGGUNAKAN METODE INTERDIGITAL COUPLE DENGAN OPEN STUB DAN DGS PADA FREKUENSI X-BAND 9,4 GHz UNTUK RADAR PENGAWAS PANTAI - Sandi, Efri; Pebriani, Melia Putri; Arifin, Maulana Ali; Akbar, Anshari (LPPM, Universitas Negeri Jakarta, 2023)
This study uses an interdigital microstrip filter design using open stub and defected ground structure for coastal surveillance radar applications. The proposed design uses the open stub method to improve bandwidth performance and defected ground structure to improve return loss and insertion loss performance. The bandwidth, return loss, and insertion loss performance of the proposed filter will be compared with conventional interdigital filter designs to determine their improvements. Numerical and simulation results show significant improvements in bandwidth, return loss, and insertion loss performance compared to conventional designs. The proposed filter design can operate in the 9.4 GHz frequency band with a bandwidth of 60 MHz, with a return loss of ≤ -10 dB and an insertion loss of ≥ -3 dB. These results prove that the proposed filter design can be used for coastal surveillance radar applications in the X-Band.